KINERJA TENAGA PENDIDIK PADA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 2 BANAWA KABUPATEN DONGGALA - Haq, Ainul (Katalogis, 2017)
This study aimed to analyze the performance of Teachers In Vocational High School (SMK) State 2 Banawa District Donggala. This research is designed qualitatively. Informants of this research are Headmaster (SMK) State 2 Banawa, Vice Principal of Curriculum, Vice Principal of Student, Teachers, Students and Supervisor of SMK State 2 Banawa who were determined using purposiveÂ with data collection methods consisted of observation, interview and documentation. As for the technical analysis of the data including data collection, data reduction, data presentation, and conclusion. The results shows that, (1) Performance of educators based on the quality of work (Quality of work) related knowledge (knowladge) and skills (skills) held by teachers in doing variations of teaching in an interesting, fun and educating students is now very good though not satisfactory and is not optimal, because there are still students who complain and do not feel satisfaction about the performance of teachers in teaching so that students feel tired and bored in the learning process. (2) Performance of educators based on the timeliness (Timeliness) in teaching and distribute report cards results of student test scores can not be said to be good, this is indicated by the behavior of the teacher often late arriving to teach, especially in the morning and at the turn of school hours, coupled with the delay of teachers in distribute report cards of students because there are still some teachers who have to deposit the results of student test scores. (3) Performance educators based initiative (Initiative) in implementing and developing character-based curriculum school in 2013, can not be said to be good. This is indicated by the unpreparedness and inability of teachers to understand, implement and develop it, because there are still some teachers who are still waiting for orders from the new boss to prepare, but it is also a lack of initiative to equip themselves by studying and seeking as much information from the media social, internet, books, syllabi or shering to fellow teachers whose schools are already implementing the curriculum in 2013. (4) Performance of educators based on the capability (Capability) in planning the preparation and implementation of the RPP can not be said to be good, this is because there are still some teachers who have not completed the preparation (RPP) which was originally to have been completed before entering the first week in the learning of the first semester of this, plus more with the non-conformance of teachers in implementing the lesson plans they have designed. Thus, in learning deliver the unfocused and in line with expectations and goals set out in the RPP, this is what causes the learning process, not running effectively and optimally.